ANALISIS RELEVANSI INFORMATION SYSTEM ARCHITECTURE BERDASARKAN KERANGKA KERJA KUALITAS MODEL ENTERPRISE ARCHITECTURE - Indah Faradhila Putri; Berlian Maulidya Izzati; Asti Amalia Nur Fajrillah (STMIK Royal, 2021)
Abstract: The development of information technology has grown rapidly and has made information systems important in running an enterprise’s business. Therefore, companies need to increasingly adopt Enterprise Architecture (EA). EA is the basis for problems that occur in an enterprise by utilizing technological innovations in meeting the expectations of information system architecture. The design quality of the Information System Architecture model has been recognized as an important factor for the success of EA design in enterprises. In meeting this quality, it is necessary to test the relevance of EA to the needs of the enterprise. This study focuses on testing the relevance of Information System Architecture design using the Enterprise Architecture Quality Framework (EAQF). The quality principle of relevance has derived attributes, which are EA Purpose and Objectives, EA Stakeholders Concerns, Usefulness, Completeness vs. Conciseness, and Level of Detail. Each attribute has an assessment method, whether qualitative, quantitative, or Yes / No. Relevance testing in this study will produce an Information System Architecture model in EA design that meets the quality principle of relevance in the EA quality framework. Keywords: Enterprise Architecture; Enterprise Architecture Quality Framework; Information System Architecture; Relevance Abstrak: Perkembangan teknologi informasi telah berkembang pesat dan menjadikan sistem informasi penting dalam menjalankan bisnis suatu perusahaan. Oleh karena itu, perusahaan perlu perusahaan semakin mengadopsi Enterprise Architecture (EA). EA merupakan landasan untuk permasalahan yang terjadi dalam suatu perusahaan dengan memanfaatkan inovasi teknologi dalam memenuhi harapan arsitektur sistem informasi. Kualitas perancangan model Information System Architecture telah diakui sebagai faktor penting untuk kesuksesan perancangan EA di perusahaan. Dalam memenuhi kualitas tersebut, maka diperlukan suatu pengujian relevansi EA terhadap kebutuhan perusahaan. Penelitian ini berfokus pada pengujian relevansi perancangan Information System Architecture menggunakan Enterprise Architecture Quality Framework (EAQF). Prinsip kualitas relevansi memiliki atribut turunan, yaitu berupa EA Purpose and Objectives, EA Stakeholders Concerns, Usefulness, Completeness vs. Conciseness, serta Level of Detail. Setiap atribut memiliki metode penilaian, baik yang bersifat kualitatif, kuantitatif, atau Ya / Tidak. Pengujian relevansi pada penelitian ini akan menghasilkan model Information System Architecture pada perancangan EA yang memenuhi standar prinsip kualitas relevansi pada kerangka kerja kualitas EA. Kata kunci: Enterprise Architecture; Enterprise Architecture Quality Framework; Information System Architecture; Relevansi